Antiracist applied linguistics, Marxian utopian, and infra politics - Setiono Sugiharto (UNIB Press, 2022)
The notion of (anti) racism in applied linguistics has been feverishly accentuated and animated, making it the buzzword du jour in the field. Drawing upon the insights generated mainly from postcolonial studies, applied linguists have become eager to resuscitate this notion, often implicitly averring that racism has long been insidiously penetrating in the field and surreptitiously operating under the so-called raciolinguistic ideologies. It is these ideologies that are alleged to perpetuate, and even to further the hegemony of White supremacy and empire, eventually giving rise to racial inequalities and racial hierarchies. The antiracism movement, it has been asserted, needs to be enacted. This article will argue that the fervent pronouncement of linguistic racism, and of antiracist movement in applied linguistics may amount to both political mystification and conceptual obfuscation of racial inequalities and racial hierarchies. Moreover, professing and even providing evidence of the existence of racism without accounting for the critiques of its intellectual basis, to which the idea of antiracism is affiliated and irrevocably rooted, is such an avant-garde endeavor that the notion masks the very fundamentals of humans as social and political beings. In the end, the article provides examples of how the so-called “racialized subjects” subvert their identities as a manifestation of doing infra politics.